The relationship between challenging behaviour and anxiety in adults with intellectual disabilities: a literature review. (21st January 2013) - Pruijssers, A. C.; van, B.; Maaskant, M.; Nijssen, W.; van, T.
Abstract Background Anxiety and challenging behaviour (CB) often occur simultaneously in people with intellectual disabilities (ID). Understanding the associations between anxiety and CB may contribute to more accurate diagnoses and management of both anxiety and CB in this population. Aims To examine the relationship between anxiety and CB. Methods A literature review covering the period from January 2000 to January 2012. Results Seven studies about the relationship between psychiatric disorders, including anxiety, and CB were identified. These studies confirm the relationship between anxiety and CB in people with ID, although the precise nature of this relationship remains unclear. Conclusions The study points toward the existence of a moderate association between anxiety and CB. Further research is needed to clarify the complex nature of the association between anxiety and CB.